Paths to purchase : the role of the online environment and the fluctuation of customer brand engagement - Saukko, Tiia (2016)
Customers´ paths to purchase are constantly developing due to digitalization. Online channels enable customers to guide their own decision processes more than ever. When understanding the complex buying journeys, companies can gain competitive advantage. Another current and interesting phenomena in the field of marketing lies in a fairly new concept called customer brand engagement (CBE). The nature of CBE has been studied to some extent, but further research is needed, especially on fluctuation, since most research focuses on observing CBE levels during a specific context and time. The aim of this research is to create insight into the customer decision-making process and CBE. The focus is on two aspects: the role of the online environment during the customer decision process and the fluctuation of CBE during the customer decision process. The customer decision process is studied from the perspective of the traditional Engel, Kollat and Blackwell (EKB) model (Engel et al. 1968), which represents the process through five steps: need recognition, information search, evaluation of alternatives, purchase decision and post-purchase behavior. The most relevant concepts in the different purchase phases, such as word-of-mouth (WOM), are also discussed. The fluctuation of CBE is studied by reflecting on the most appropriate studies concerning the concept. The nature of this study is a qualitative study with an abductive approach. The empirical material comes from thirty semi-structured interviews conducted among customers who purchased from Brands A and B that operate in the renovation field selling windows and doors. The data is analyzed through content analysis. Based on the results, the nature of CBE is fluctuating, which is supported by earlier studies. Fluctuation of CBE was found to be caused by the fluctuation of interactivity between brand and customer. Interestingly, half of the informants were not engaged at all. The role of the online environment varied depending on the purchase phase and it was most significant during active information search. The role of face-to-face contact with a brand representative and the effect of traditional WOM were stronger than expected. In sum, this study suggests that companies should focus on interacting with customers throughout the entire decision process.